Transformation towards sustainable development goals: Role of innovation ecosystems for inclusive, disruptive advances in five Asian case studies - Michiko Iizuka; Gerald Hane (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2021)
The transformation of sociotechnical systems is considered necessary for achieving the Sustainable Development Goals(SDGs). However, this transformation process is inhibited by institutional inertia of the public sector, vested interests of the private sector, routine habits of individuals, and increased complexity of globalised activities. While policies to stimulate the transition exist, these policies and pathways are still considered insufficient. Meanwhile, there are many individual private initiatives taking place to advance the societal agenda. Although these are still isolated actions of new actors, they have the potential to become broader movements bringing disruptive advances through innovation. This study explores the potential of innovation ecosystem to understand the emerging private sector initiatives to meet social agenda through innovations that are disruptive and inclusive. Four types of businesses are examined: venture capital, an incubator, venture start-ups, and a social impact fund. A common feature underlying these cases are the creation of tailored innovation ecosystems that effectively utilises complementary assets. Currently these activities are self-generated without much government support. However, by aligning with public policy impact can be accelerated towards achieving the SDGs. Examining cases as 'signals' provide hints for how policy can be formulated to scaled-up and transform currently isolated private initiatives.
Keywords: O32; O35; O38; M13; 330; Innovation Ecosystems; SDGs; Emerging business; Complementary assets; Transformative change; Asia